2023
DOI: 10.1186/s12951-023-01776-8
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound targeted microbubble destruction-triggered nitric oxide release via nanoscale ultrasound contrast agent for sensitizing chemoimmunotherapy

Abstract: Immunotherapy had demonstrated inspiring effects in tumor treatment, but only a minority of people could benefit owing to the hypoxic and immune-suppressed tumor microenvironment (TME). Therefore, there was an urgent need for a strategy that could relieve hypoxia and increase infiltration of tumor lymphocytes simultaneously. In this study, a novel acidity-responsive nanoscale ultrasound contrast agent (L-Arg@PTX nanodroplets) was constructed to co-deliver paclitaxel (PTX) and L-arginine (L-Arg) using the homog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…In another study [ 171 ] more skillfully combined SDT, NO gas therapy with chemotherapy, they prepared nanodroplets that co-delivered paclitaxel and L-arginine (L-Arg) by homogenization/emulsification method. The bubbles generated by L-Arg@PTX nanodroplets under ultrasound can greatly promote the release and accumulation of sonosensitizers in deep tissues, and the cavitation effect can reduce the cavitation threshold intensity of SDT.…”
Section: Isdt For Cancermentioning
confidence: 99%
“…In another study [ 171 ] more skillfully combined SDT, NO gas therapy with chemotherapy, they prepared nanodroplets that co-delivered paclitaxel and L-arginine (L-Arg) by homogenization/emulsification method. The bubbles generated by L-Arg@PTX nanodroplets under ultrasound can greatly promote the release and accumulation of sonosensitizers in deep tissues, and the cavitation effect can reduce the cavitation threshold intensity of SDT.…”
Section: Isdt For Cancermentioning
confidence: 99%
“…Under low-intensity ultrasound, they produce a series of biological effects, thereby mediating drug delivery, gene transfection, tissue barrier opening, immunotherapy, and so on, laying a solid foundation for precision treatment, forming "one-stop precise diagnosis and treatment" model that integrates early diagnosis, targeted therapy, and efficacy evaluation of tumors. 1145 For instance, Li et al 249 reported the application of UTMD technology combined with nanoscale ultrasound contrast agents in the effective controlled release of NO and its sensitized tumor chemotherapy immune combination therapy. In this study, O-carboxymethyl chitosan with exogenous ultrasound-responsiveness and endogenous acidity-responsiveness was used as the shell, and PFH, which can achieve ultrasonic contrast, was used as the core to prepare a nanoscale ultrasound contrast agent (L-Arg@PTX nanodroplets) that combined chemotherapy drugs and NO donors.…”
Section: Ultrasound-mediatedmentioning
confidence: 99%
“…Studies have demonstrated that several chemotherapeutic agents, including doxorubicin, cisplatin, oxaliplatin, and paclitaxel can induce apoptosis in tumor cells as well as elicit ICD via ERS response. 42 Dying tumor cells following specialized chemotherapeutics can trigger ICD to facilitate CALR translocation on the surface, which is considered an "eat me signal" for APCs. In addition, dying tumor cells release ATP and HMGB1 to activate DCs.…”
Section: Icd Induced By Chemotherapeutic Agentsmentioning
confidence: 99%